Rozważania na temat zawartości i okoliczności ukrycia tzw. skarbu bydgoskiego - Grupa, Małgorzata; Jarzęcki, Krzysztof (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2024)
The article presents the so-called ‘Bydgoszcz treasure’ – the artefacts excavated during systematic archaeological exploration conducted in Bydgoszcz cathedral in January 2018. Preliminary analyses of its contents — coins, devotional objects, and jewellery — have established the time range of these objects’ origin as approximately 157 years (1495–1652). The characterisation of the artefacts yielded various possibilities for interpreting the discovered jewels. The collected information formed the basis for identifying the bourgeoisie or local nobility as potential holders of the property. The timing of the completion of the coin collection (1652) suggests that, during a time of war threat, the collected property was placed under the floor of the church of St Martin and St Nicholas. The owner may have died without informing anyone of its deposition.
ill. ; 23 cm
Keywords: cathedral; archaeology; sixteenth century; seventeenth century; Old Polish culture; hoard